Discursive Constructions of Women’s Bodies: A Critical Discourse Analysis of Autonomy and Empowerment in Pakistan - Majeed, Asma; Malik, Raana; Hamdani, Asima Riaz (Pakistan Languages and Humanities Review, 2025)
This paper conducts a critical discourse analysis of the discursive constructions of women’s autonomy and empowerment in Pakistan, limited to the selected articles from three online Urdu weblogs (2019-2021). The study is contextualized by the societal clash between feminist and traditionalist ideals, where discourses on both sides paradoxically contribute to women’s objectification. Using Fairclough’s three-dimensional model of Critical Discourse Analysis, the study deconstructs underlying ideologies within and between the texts. Results indicate the concept of autonomy is fluid and ideologically driven, creating a central paradox where competing narratives converge on objectifying women. The analysis highlights profound ambiguity in key slogans and a disconnect between perceived and actual autonomy. It is recommended that public discourse move beyond simplistic binaries toward greater conceptual clarity. Future advocacy should critically assess rhetorical strategies to avoid perpetuating objectification, necessitating the development of alternative discursive frameworks for discussing women’s agency.